Auto-component industry in Asia: structure, trade patterns and potential for further upgrading. (12th December 2008) - Nag, Biswajit
During the second half of the 1990s, the globalisation of the automotive industry has greatly accelerated. Asian economies are the latest production destinations as well as consumption centres. These countries are also major exporters of automobiles and auto components. Due to structural change in the automobile industry, the ancillary sector is morphing into system sub-suppliers and component manufacturers. They are now sharing risks significantly along with the original equipment manufacturers. Component sectors in many Asian countries are increasingly less protected and competition is now intense. At this juncture, the paper analyses the growth and trade dynamics of automotive sector in some Asian countries focusing on the industrial structure and the layers of the value chain. The paper studies the trade pattern of automobile and component industry and discusses the flow of intra-Asian trade in components and its nuances. It also has made an attempt to explore the role of regional trade liberalisation in enhancing the trade of auto-components.